Early Management of Aspiration Pneumonia in an Infant With Suspected Laryngomalacia in A Resource-Limited Setting: A Case Report - Vita, Angelica Diana; Mahyuddin, Muhammad Hanun; Saraswati, Dian (Journal of Community Medicine and Public Health Research, 2025)
Laryngomalacia is the most common cause of congenital stridor in infants and can lead to feeding difficulties, failure to thrive, and respiratory distress. Diagnosis typically requires flexible fiberoptic laryngoscopy, which more often than not, not available in resource-limited settings. We report a 12-day-old male infant who presented to the emergency department with apnea following a choking episode. He required cardiopulmonary resuscitation and was admitted to the neonatal intensive care unit. Clinical findings included chest retractions, cyanosis, weight loss (from 3500g at birth to 2700g), and feeding difficulties. Chest radiograph showed right-sided perihilar infiltrates consistent with aspiration pneumonia. Despite initial clinical improvement, the infant developed new-onset positional stridor on day ten of hospitalization, particularly when supine. These findings raised strong suspicion of underlying laryngomalacia. These signs raised a strong clinical suspicion of laryngomalacia. Due to absence of flexible fiberoptic laryngoscopy, diagnosis could not be confirmed. The infant was stabilised with supportive care and feeding adjustments before being referred to a tertiary center for definitive evaluation and management. This case highlights the importance of prompt recognition and early stabilisation of neonates with aspiration-related complications and suspected airway anomalies, particularly in low-resource settings. Timely referral is essential to prevent deterioration and guide appropriate long-term management.